Studies on the Role of Fibrinolysis and Fibrinogen Degradation Products (FDP) in Analgesic Action of Morphine - Buczko, Włodzimierz; Wiśniewski, Konstanty (Thrombosis and Haemostasis, 1972)
The role of fibrinolysis and FDP in the analgesic action of morphine in mice and rats was studied. It was shown that during activation of blood fibrinolysis, both the accumulation of morphine in the brain tissue of rats and the clinical effect of this drug were increased. Similar results were observed after morphine given simultaneously with FDP obtained in vitro. The data from the analysis of FDP carried out on Sephadex G-25 Fine columns suggest that only FDP of molecular weight of about 10,000 potentiate the action of morphine; smaller peptides decreased the action of this drug.